Traditional and novel cardiometabolic risk markers across strata of body mass index in young adults - Mia Klinkvort Kempel (Wiley, 2021)
Abstract Background Cardiometabolic risk increases with increasing body mass index (BMI). The exact mechanism is poorly understood, and traditional risk assessment of young adults with obesity has shown to be ineffective. Greater knowledge about potential new effective biomarkers and the use of advanced cardiac imaging for risk assessment in young adults is, therefore, necessary. Objective This study aims to explore traditional and novel cardiometabolic risk markers across strata of BMI in young adults. Methods Participants (N = 264, 50% women, age 28–30 years) were invited from an ongoing cohort study, based on BMI and sex. BMI‐strata were: BMI <25, 25–30, >30 kg/m2, representing normal weight (NW), overweight (OW), and obesity (OB). Participants underwent cardiac computed tomography to detect coronary artery calcification, measures of body composition, blood pressure measurements, and a comprehensive panel of circulating cardiometabolic risk markers. Results No significant coronary artery calcifications were detected in this study. Minor differences in median levels of traditional risk markers were detected across BMI‐strata, for example, total cholesterol (men‐ NW: 4.7 (4.3–5.1) and OB: 4.8 (4.2–5.6) mmol/L, p = 0.58; women‐ NW: 4.3 (3.9–4.8) and OB: 4.7 (4.2–5.3) mmol/L, p = 0.016), whereas substantial differences were seen in markers of inflammation and glucose metabolism, for example, high sensitive CRP (men‐ NW: 0.6 (0.3–1.1) and OB: 2.8 (1.5–4.0) mg/L, p < 0.001; women‐ NW: 0.7 (0.3–1.7) and OB: 4.0 (2.2–7.8) mg/L, p < 0.001) and insulin (men‐ NW: 47.0 (35.0–59.0) and OB: 113.5 (72.0–151.0) pmol/L, p < 0.001; women‐ NW: 44.0 (35.0–60.0) and OB: 84.5 (60.0–126.0) pmol/L, p < 0.001). Conclusion In young adults, obesity is associated with an early onset insulin resistance and inflammatory response prior to development of coronary artery calcification and deterioration of lipid profiles.